The Landscape of MOOC Platforms Worldwide - Perifanou, Maria; Economides, Anastasios A. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2022)
Previous studies have mainly investigated major massive open online course (MOOC) platforms such as Coursera, edX, and Udemy. This study used 21 metrics to explore 35 MOOC platforms from across the world. Five Web analytics tools were used to analyze these MOOC platforms using data from MOOC platform directories and exploration of platform sites. The findings revealed that many universities, companies, and organizations have cooperated with the platforms and provided MOOCs through them. Major global platforms have offered thousands of MOOCs while regional platforms were more likely to have offered dozens. Some large platforms had millions of registered users while others registered just thousands. The major global platforms were established in the US to offer MOOCs mainly in English, though they offered MOOCs in other languages as well. The regional platforms offered MOOCs mainly in local languages, and to some extent in English and other languages. Some platforms engaged users for long periods while others failed to keep users after they viewed the first page of the platform. On average, a visitor stayed on a platform for 8 minutes visited 7.2 pages per visit. Major global platforms attracted users from all over the world, while regional platforms mainly attracted users from countries where the regional platform language was spoken. Some platforms had very few accessibility and contrast errors while other platforms performed poorly. Most platforms were mobile-friendly. However, administrators of almost all MOOC platforms should take actions to increase the speed of their platform. Other recommendations include undertaking marketing campaigns to increase the number of partners, the number of MOOCs offered, and the platforms’ visibility.